Kinematic characteristics of the backstroke swimming technique of the qualified swimmers with the effects of cerebral palsy - Vasiliy Bosko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to determine kinematic characteristics of backstroke swimming technique of athletes with spastic cerebral palsy (CP). Material & Methods: 12 swimmers with consequences of cerebral palsy were involved in the experiment (level of sports qualification - master of sports and candidate of master of sports); Video shooting and computer video analysis of their technique of backstroke swimming; The obtained data were analyzed and generalized using the methods of mathematical statistics. Results: kinematic characteristics of the technique of backstroke swimming of disabled athletes with spastic diplegia and a hemiparetic form of CP, such as the body position of swimmer in water (angle of attack, angle of rotation of the trunk around the longitudinal axis), position and work the hands and feet of the swimmer (the angles of flexion the main joints and their movement), integral characteristics (cycle time, step, rate and ratio of these characteristics at a constant swimmer speed). Conclusions: determined biomechanical characteristics motions skilled swimmers with spastic CP forms, which indicate the specificity of their technique of backstroke swimming, so we recommend that you take into account the findings in the search for effective means and methods of sports training.